The Effect of Pop Up Book Activities On Group A's Early Childhood Creativity - Anisa Fera Hidayah (Department of Early childhood Education, 2020)
This research shows determine whether there is influence of activity pop up book to the creativity of children ages early in TK Pertiwi Kwarasan Years Doctrine 2018/2019. Based on the results of the research can be concluded that the activities of the pop-up book effect on the creativity of children aged early group A. The results of the analysis of the data of research that has been carried out , obtaining the results of scores observation of early development of the creativity of the child before conducted an experiment with the activities of the pop-up book is amounted to 169 with an average of 15.36, the value of the highest 21, the value of the lowest 12 and Standar Deviation = 3.264.